2016
DOI: 10.5812/iranjradiol.21186
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in the Evaluation of Cytologically Indeterminate Thyroid Nodules

Abstract: Background:Thyroid nodules with indeterminate fine-needle aspiration biopsy (FNAB) results remain a diagnostic dilemma, because 70 - 85% of these nodules have been found to be benign after thyroid surgery.Objectives:The purpose of this study was to evaluate the usefulness of 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in the preoperative diagnosis of cytologically indeterminate nodules.Patients and Methods:Forty-six patients were included in this study. These individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, there is inconsistent information about the diagnostic role of SUV max values for determining malignancy. Some studies have shown no significant difference between the SUV max values of benign and malignant thyroid nodules (16)(17)(18), whereas numerous others have suggested its usefulness for identifying malignant lesions (14,19,20). The importance of SUV max and its definitive cut-off value for predicting malignancy have not yet been established among patients with 18F-FDG PET/CT-positive thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is inconsistent information about the diagnostic role of SUV max values for determining malignancy. Some studies have shown no significant difference between the SUV max values of benign and malignant thyroid nodules (16)(17)(18), whereas numerous others have suggested its usefulness for identifying malignant lesions (14,19,20). The importance of SUV max and its definitive cut-off value for predicting malignancy have not yet been established among patients with 18F-FDG PET/CT-positive thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence noting the differentiation between Hürthle cell carcinoma and follicular adenomas on PET [ 84 , 85 ]. In a study enrolling 46 patients with indeterminate results on FNA, which surveyed the efficacy of PET/CT for detecting malignant lesions, the sensitivity, specificity, and positive predictive and negative predictive values were 94%, 62%, 59%, and 95%, respectively [ 86 ]. Pre-ablative 18 FDG-PET is helpful for the further assessment of malignant FDG-avid LNs in patients with PTMC or papillary thyroid carcinoma (PTC) [ 86 ].…”
Section: Indicationsmentioning
confidence: 99%
“…In a study enrolling 46 patients with indeterminate results on FNA, which surveyed the efficacy of PET/CT for detecting malignant lesions, the sensitivity, specificity, and positive predictive and negative predictive values were 94%, 62%, 59%, and 95%, respectively [ 86 ]. Pre-ablative 18 FDG-PET is helpful for the further assessment of malignant FDG-avid LNs in patients with PTMC or papillary thyroid carcinoma (PTC) [ 86 ]. For patients who have low-SUV follicular neoplasms (SUVmax <5) and are unsuitable or unwilling to undergo surgery, RFA could be a viable alternative [ 85 ].…”
Section: Indicationsmentioning
confidence: 99%
“…Thus, the sensitivity of 18 FDG-PET in identifying malignant tumors > 1 cm is high (Kresnik et al 2003, Kim et al 2007, Sebastianes et al 2007, Traugott et al 2010, Muñoz Pérez et al 2013, Buyukdereli et al 2016, Pathak et al 2016, Piccardo et al 2016.…”
Section: F-fluorodeoxyglucose Positron Emission Tomographymentioning
confidence: 99%